How I do it: modified lichtenberger-brown tracheoesophageal puncture procedure - Nikolay R. Sapundzhiev; Asen G. Asenov; Blagovesta Spasova; Petya S. Genova; Georgi I. Davidov; Darina Ivanova (Journal of Otolaryngology - Head and Neck Surgery, 2022)
Abstract Background Tracheoesophageal puncture (TEP) with use of a prosthesis is nowadays a standard for voice restoration after laryngectomy. Different TEP approaches exist. Methods We retrospectively reviewed our series of patients who underwent TEP by a novel technique, based partially on the Lichtenberger endo-extralaryngeal needle carrier. The instrument is covered with a protective Nelaton catheter and introduced via the mouth to the neopharynx/esophagus. No rigid endoscope is used for visualization of the TEP site. The tip is palpated through the stoma at the posterior tracheal wall and incision is done to the catheter tip. The prosthesis is introduced through the mouth and the neopharynx in a retrograde fashion. Results In 14 laryngectomees with postoperative radiation voice prosthesis was successfully placed with this technique. A total of 18 procedures were performed. One misplacement occurred. No other early or late complications were observed or any other TEP or prosthesis related problems. Conclusions The rationale of our technique is to simplify the procedure, avoid risk-bearing approaches and instruments such as rigid endoscopes, simplify the armamentarium and reduce tissue trauma. The initial clinical experience in 18 TEPs confirmed it usefulness in both standard and anatomically challenging situations. Trial registration The current study obtained the ethical approval from the Faculty of Medicine at Medical University "Prof. Dr. Paraskev Stoyanov"—Varna, Bulgaria (Protocol 087/24.10.2019 (retrospectively registered). Graphical abstract